(untitled) (Fiep Bulletin - online, 2020)
Currently, many students report to the core manager and teachers of the EEMTI Adahil Barreto Cavalcante, challenges centered on the emotions that result in daily conflicts that affect directly in the teaching and learning process, such as: depression, anxiety, low self-esteem, among others . The lack of emotional control in the face of challenging situations, for example, the achievement of the National High School Examination (ENEM) instigated the school’s managerial nucleus to encourage innovative practices that work with students’ emotional control and self-knowledge in classrooms. PE. But can Cooperative Games help in the control and recognition of emotions? The objective was to promote experiences that used the Cooperative Games as a tool for conflict resolution and the exercise of self-knowledge. The actions were developed in 2019, using a ludiform methodology, such as: cooperative driving challenges. We conducted the research with the three groups of third year of high school, with a weekly meeting. We used questionnaires, observation of the participants and production of photographic images. It is concluded that the actions that exalt the work on emotions in the school are relevant and essential for the integral formation of the students, since the recognition and the emotional control make possible a meaningful learning in the educational process.